Psychology Students’ Career Adaptability as Predictor Employability in Public Health Systems - Olievia Prabandini Mulyana, Nur Hidayah , Nur Eva , Ninik Setiyowati, Amin Al Haadi Shafie (South Eastern European Journal of Public Health, 2025)
Psychology students have great potential to contribute to future public health programs through their role in mental health. This study aims to look at the influence of career adaptability on employability in psychology students. This study is quantitative method research using linear regression analysis. This study involved 518 psychology students from one of the state university in Indonesia. The results of regression analysis show significant results and career adaptability has an influence contribution of 40% in influencing student employability. Based on these results, it is known that the hypothesis of this study is accepted, career adaptability can be a positive predictor that can increase student employability.